2006
DOI: 10.1002/fedr.200611106
|View full text |Cite
|
Sign up to set email alerts
|

Molecular data (nrITS‐sequencing) reveal relationships among Iranian endemic taxa of the Umbelliferae

Abstract: The majority of endemic and subendemic Iranian Umbelliferae taxa have never been investigated using molecular approachs to phylogeny. 36 species from 28 genera of the Umbelliferae from this region were included for the first time in analysis using ITS sequence data to clarify their systematics. For some newly investigated (Leiotulus, Semenovia, Ducrosia, Echinophora, Pycnocycla, Turgenia lisaeoides, Prangos, Alococarpum, Bilacunaria, Elaeosticta, Johreniopsis, Pseudotrachydium) taxa the molecular data correspo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(20 citation statements)
references
References 25 publications
(18 reference statements)
2
18
0
Order By: Relevance
“…Similarly, the Iranian endemic species Opsicarpium insignis also falls within the Pimpinella ‘core group’. Previously, Valiejo‐Roman et al () reported that Pimpinella and Opsicarpium are close genera based on molecular data, a relationship supported by their similar fruit structure and pinnate leaves. Our results corroborate the inclusion of Opsicarpium into Pimpinella .…”
Section: Discussionmentioning
confidence: 92%
“…Similarly, the Iranian endemic species Opsicarpium insignis also falls within the Pimpinella ‘core group’. Previously, Valiejo‐Roman et al () reported that Pimpinella and Opsicarpium are close genera based on molecular data, a relationship supported by their similar fruit structure and pinnate leaves. Our results corroborate the inclusion of Opsicarpium into Pimpinella .…”
Section: Discussionmentioning
confidence: 92%
“…Their close relationship was confirmed using immunological comparisons of seed-storage proteins (Shneyer & al., 1995). In contrast, the first ITS sequence analyses placed Dorema, represented by a single accession of D. aucheri Boiss., as sister group to Seseli mucronatum (Schrenk) Pimenov & Sdobnina in tribe Selineae distant from Ferula (Valiejo-Roman & al., 2006). This result was probably due to sample contamination or voucher misidentification because subsequent molecular studies confirmed that Dorema is closely related to Ferula (Ajani & al., 2008;Kurzyna-Młynik & al., 2008).…”
Section: Introductionmentioning
confidence: 99%
“…This paper is the second contribution in the series regarding the nomenclature of the Italian vascular flora and other phanerogams, following on a preliminary note and an observation on the genus Vachellia (Banfi & Dichoropetalum Based on analyses of the ITS sequences, the genus Holandrea, already recently separated from Peucedanum, has been transferred to Dichoropetalum Fenzl together with other species of Peucedanum s.l., all grouped as belonging to the SE-European-SW-Asiatic chorotype (Valiejo-Roman et al, 2006;Pimenov et al, 2007). The following species are recognised in Italy.…”
Section: Introductionmentioning
confidence: 99%